Elephantine Revisited and Elephantine in Context A Review Article - Ziemba, Kacper (2023)
Review article of Elephantine Revisited: New Insights into the Judean Community and Its Neighbors and Elephantine in Context: Studies on the History, Religion and Literature of the Judeans in Persian Period Egypt. The article reviews two recently published volumes on Elephantine in the Persian period. It presents their content, describes advances in studies and suggests how we can go further in research.
Keywords: Rezension